Produção do espaço rural e as marcas na paisagem do Pampa gaúcho: os olivais no município de Caçapava do Sul/RS - Beling, Helena Maria (2022)
This research presents thoughts on the production of rural areas and the transformations on the landscape of Pampa Gaúcho, embracing the specific case of olive groves and its insertion, development and expansion in the municipality of Caçapava do Sul/RS. The time gap starts in 2005, when olive growing began in the municipality, as well as in the state of Rio Grande do Sul. The general goal was to comprehend how the expansion of olive trees in the Pampa Gaúcho and in the municipality of Caçapava do Sul/RS has been occurring. Specifically, the intentions were to understand the origin, the importance in the most distinct spaces and times, the transformations occurred in the rural space, the marks on the landscape, the introduction period, the people involved, the challenges, the perspectives, the policies and development programs, besides the dialogue between subjects and agents involved with olive growing. This investigation was based on a qualitative approach. We rely on bibliographical and documental investigation, relevant to the topic and area of inquiry and to the field research. During the fieldwork, we used systematic and nonparticipant observation, semi-structured interviews, field journals, photographic collection and, by the end, we analyzed and discussed the information and data collected. The fieldworks and techniques used in the research were performed with olive growers from Caçapava do Sul/RS, with counselors of the olive oil industries in the municipality and with agencies/institutions of the aforementioned state and municipality. The rapprochement with the interviewed people allowed us to apprehend the diversity, the heterogeneity and the uniqueness of olive growing in Caçapava do Sul/RS. Olive production is recent in the state so Caçapava do Sul is a pioneer in the insertion of orchards. According to the edaphoclimatic zoning of olive growing for the state, there are significant areas suitable for cultivation. There are many obstacles experienced by the producers, especially in the first years of the olive groves. Production in the state is still unstable and presents several challenges and problems, but much progress has been made and the prospects are good. Policies, programs and technical assistance aimed at production are extremely important to strengthen, ensure quality and economic return to the producers. The production of olives and the insertion of the olive oil industries in Caçapava do Sul/RS enabled a new dynamic, besides productive, social and economic diversification in the municipality, being a source of work and income.